2007
DOI: 10.1007/978-3-540-73335-5_13
|View full text |Cite
|
Sign up to set email alerts
|

A Distributed Framework for Scalable Large-Scale Crowd Simulation

Abstract: Abstract. Emerging applications in the area of Emergency Response and DisasterManagement are increasingly demanding interactive capabilities to allow for the quick understanding of a critical situation, in particular in urban environments. A key component of these interactive simulations is how to recreate the behavior of a crowd in real-time while supporting individual behaviors. Crowds can often be unpredictable and present mixed behaviors such as panic or aggression, that can very rapidly change based on un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…A review of existing hybrid models for pedestrian simulation can be found in the study by Ijaz, Sohail, and Hashish (2015). More studies recently have focused on developing computational architectures that can cope with largescale crowd modelling, including those by Lozano et al (2007) and by Fernandez et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…A review of existing hybrid models for pedestrian simulation can be found in the study by Ijaz, Sohail, and Hashish (2015). More studies recently have focused on developing computational architectures that can cope with largescale crowd modelling, including those by Lozano et al (2007) and by Fernandez et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, crowd simulations have become an essential tool for many virtual environment applications in education, training, and entertainment [4,12,5]. These applications require both rendering visually plausible images of the virtual world and managing the behavior of high number of autonomous agents.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation is then divided up with the set of agents and/or environment being shared equally amongst the machines. Distribution has been applied to agent-based crowd simulations previously (Lozano et al 2007) with promising results. However, distribution introduces its own challenges.…”
Section: Introductionmentioning
confidence: 99%